Chemotherapy With or Without Maintenance Sunitinib for Untreated Extensive-Stage Small-Cell Lung Cancer: A Randomized, Double-Blind, Placebo-Controlled Phase II Study-CALGB 30504 (Alliance) - Ready, Neal E; Pang, Herbert H; Gu, Lin; Otterson, Gregory A; Thomas, Sachdev P; Miller, Antonius A; Baggstrom, Maria; Masters, Gregory A; Graziano, Stephen L; Crawford, Jeffrey; Bogart, Jeffrey; Vokes, Everett E (Journal of clinical oncology, 2015)
To evaluate the efficacy of maintenance sunitinib after chemotherapy for small-cell lung cancer (SCLC). The Cancer and Leukemia Group B 30504 trial was a randomized, placebo-controlled, phase II study that enrolled patients before chemotherapy (cisplatin 80 mg/m(2) or carboplatin area under the curve of 5 on day 1 plus etoposide 100 mg/m(2) per day on days 1 to 3 every 21 days for four to six cycles). Patients without progression were randomly assigned 1:1 to placebo or sunitinib 37.5 mg per day until progression. Cross-over after progression was allowed. The primary end point was progression-free survival (PFS) from random assignment for maintenance placebo versus sunitinib using a one-sided log-rank test with α = .15; 80 randomly assigned patients provided 89% power to detect a hazard ratio (HR) of 1.67. One hundred forty-four patients were enrolled; 138 patients received chemotherapy. Ninety-five patients were randomly assigned; 10 patients did not receive maintenance therapy (five on each arm). Eighty-five patients received maintenance therapy (placebo, n = 41; sunitinib, n = 44). Grade 3 adverse events with more than 5% incidence were fatigue (19%), decreased neutrophils (14%), decreased leukocytes (7%), and decreased platelets (7%) for sunitinib and fatigue (10%) for placebo; grade 4 adverse events were GI hemorrhage (n = 1) and pancreatitis, hypocalcemia, and elevated lipase (n = 1; all in same patient) for sunitinib and thrombocytopenia (n = 1) and hypernatremia (n = 1) for placebo. Median PFS on maintenance was 2.1 months for placebo and 3.7 months for sunitinib (HR, 1.62; 70% CI, 1.27 to 2.08; 95% CI, 1.02 to 2.60; one-sided P = .02). Median overall survival from random assignment was 6.9 months for placebo and 9.0 months for sunitinib (HR, 1.28; 95% CI, 0.79 to 2.10; one-sided P = .16). Three sunitinib and no placebo patients achieved complete response during maintenance. Ten (77%) of 13 patients evaluable after cross-over had stable disease on sunitinib (6 to 27 weeks). Maintenance sunitinib was safe and improved PFS in extensive-stage SCLC.